Design and Development of Online Cooperative Management System for Sekolah Menengah Kebangsaan Muadzam Shah - Wan Junizam, Wan Ikmal Azizi; WAHID, NORFARADILLA (Applied Information Technology And Computer Science, 2026)
The Online Cooperative Management System for SMK Muadzam Shah is a web-based platform designed to help parents and cooperative staff manage school cooperative tasks more efficiently. It replaces outdated manual processes such as product listing, administrative management, and user tracking that often led to delays and miscommunication. The system improves accessibility, streamlines operations, and enhances user engagement through a modern and user-friendly interface. Developed using PHP, HTML, CSS, and MySQL, the platform ensures secure and reliable data management. The project followed the Prototype Model, allowing for iterative improvements based on user feedback. The final system offers smoother transactions, better communication between stakeholders, and a significant improvement in cooperative operations. System testing confirmed that it meets user needs and provides a seamless experience. This project marks a meaningful shift toward digital transformation in school-based cooperative management.